Communication, coordination and cooperation in construction projects: Business environment and human behaviours - Alaloul, W.S. (Institute of Physics Publishing, 2018)
The accomplishment of construction projects is extremely dependent on the integration of several stakeholders; therefore none of them has the control or the ability to accomplish the project alone. Each of them may influence and be influenced by the project management approach. There is no comprehensive theoretical platform for defining Communication, Coordination and Cooperation (3Cs) in the management of construction project. This paper deliberates the function of the 3Cs different theoretical perceptions. Through an analysis of selected articles from reputable academic journals in construction management, the business environment and human behaviour were identified as two main parts. A little has been done so far about the 3Cs, and how they are correlated with construction projects performance. Therefore, the objective of this paper is to explain the definitions and the association between the 3Cs. There is a significant link between communication and coordination. Coordination alternatively, is trust-based a logic of mutual and exchange. Consequently, cooperation is much more sophisticated, which needing more time and attempts. Â© Published under licence by IOP Publishing Ltd.